Peran Aplikasi Pegadaian Digital Service (PDS) dalam Mempermudah Transaksi dan Layanan Milenial di PT Pegadaian Sumbawa - Pratama, Ari; Rakhmatullah, Vivin Nila (Lembaga Yasin AlSys, 2024)
Pegadaian is a state-owned company that has been established since 1905 and is currently 123 years old. This company is one of the most developed companies in Indonesia, including in the city of Sumbawa, West Nusa Tenggara Province. This is indicated by the increasing number of branch offices and UPCs on the island of Sumbawa which are very easy to find. PT. Pegadaian continues to innovate pawn products to attract consumers and increase company profits. In line with this, the number of consumers has also increased drastically because of the various conveniences offered by PT. Pegadaian with the slogan